The executive guide to understanding and implementing employee engagement programs : expand production capacity, increase revenue, and save jobs - Townsend, Patrick L. (ASQ Quality Management Division economics of quality book series., 2007)
"This book is for anyone who is currently in a position to impact the future of an organization - or anyone who hopes to be in a position to lead or support such an effort in the future. This includes not only for-profit business enterprises, but any organization. For many, this approach to performance excellence will require a willingness to rethink their approach both to other people and to the workplace. Once you head down this path, everything changes."--Jacket